Effect of cognitive multisensory rehabilitation on upper extremity function in stroke patients: A randomized controlled trial - Lama Saad El-Din Mahmoud; Omnia Shokry Mohamed; Osama Yacoub; Mohammad Sadik Badawy (Sport TK, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.